Personality in faces: Implicit associations between appearance and personality. (27th September 2018) - Jones, Alex L.; Tree, Jeremy J.; Ward, Robert
Abstract: How accurate are the spontaneous trait inferences made to faces? Here we measured implicit associations between facial appearance and personality traits, using faces conveying objective appearances of Extraversion and Agreeableness. In the standard or "uncrossed" conditions of Experiment 1, we found that descriptions of high and low Agreeableness and Extraversion were spontaneously and accurately associated with their objective trait appearance. In Experiment 2, to test the specificity of this effect, we "crossed" the Implicit Association Tests, pairing faces conveying high and low Extraversion with words describing characteristics of high and low Agreeableness, and the reverse. We found evidence for associations specific to objective appearance of Agreeableness, and a general halo effect relating to Extraversion. We conclude that spontaneous assessment of personality from faces can be accurate, and can be based on trait‐specific as well as general visual cues.